Application of Grape Stems Extract to Increase the Antioxidant Capacity of Whiskey - Anatoliy Kazak; Yurij Grishin; Joel B. Johnson; Nikolay Oleinikov; Marina Rudenko; Angela Mayorova; Anna Dorofeeva; Kristina Frolova (International Journal of Food Science)
The recent steady demand for products with increased antioxidant properties largely determines the direction of research in the field of creating high-quality products with increased biological value. Insufficient knowledge of the antioxidant activity and potential biological value of whiskey makes this area of research relevant and in demand. This study presents the results of an analysis of the influence of distillate aging conditions on the phenolic composition and antioxidant capacity of whiskey, obtained using coulometric, chromatographic, and amperometric methods of analysis. During the study, samples of whiskey with increased antioxidant capacity were obtained based on the use of alcoholic extracts of grape stems of the Vitis vinifera species. The data obtained as a result of the study can be used in the future both to improve the efficiency of methods for monitoring and regulating the circulation of alcoholic products based on the developed methodology for determining antioxidant capacity and to contribute to the creation of a new type of alcoholic products with an increased content of bioavailable biologically active substances and antioxidant capacity.